Effect of Body Function and Recognition for Body Function on the Movement Strategy of Older Adults in an Obstacle Avoidance Task - SUDO, Daisuke; YAMAMOTO, Sumiko; HARAGUCHI, Rikiya; KAGEYAMA, Tsuyoshi (Physical Therapy Japan, 2021)
Purpose: In recent years, the effect of visual function and recognition for body function on the movement of elder subjects has been investigated. The purpose of this study was to clarify the effect of body function and the recognition for body function on the movement strategy in an obstacle avoidance task designed for older adults.Methods: Twenty older adults and 12 young adults participated in this study. They were told to walk along a 5-m pass and go through the gap with various width. The movement was recorded using a 3D motion capture system and the duration of gaze was measured using an eye mark recorder. Older participants were categorized based on physical assessment findings:, Low risk (LR) group and High risk (HR) group. To identify the level of recognition for body function, older participants were asked to assess whether they could go through the gap without rotating the body. According to the answer, these participants were further categorized as, correct and incorrect.Results: Our findings showed that, in the LR and HR groups, the stride length reduced while passing through narrow gaps (gap width < body width), and the angle of rotation was greater in the HR group than in the LR group.Conclusion: The results suggest that body function and body recognition influenced the kinematic changes and obstacle gaze time in obstacle avoidance movements performed by older adults.